Tradisi Mamapas Lewu Sebagai Perwujudan Nilai-Nilai Toleransi di Masyarakat Desa Hanjak Maju - Susanto, Deri (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
The values ​​contained in the mamapas lewu tradition include willingness to sacrifice, mutual cooperation, respect for God, mutual cooperation, expression of gratitude, self-purification, self-control, eliminating envy, envy and revenge and loyalty to promises. In context, other tribes may just be making small talk as an effort to bring closer relations with others. But the Dayak people need free space to express their culture and traditions. In other words, the Dayak tribe needs traditions to create space for others. If we look closely, each tribe has a different perception of seeing the same reality regarding the placement of themselves towards other people. Dayak people tend to distance themselves and withdraw, while other tribes tend to eliminate distance at the level of social relations. In this way, eating lewu can eliminate social distance between people in society. The aim of the tolerance values ​​contained in the mamapas lewu tradition is that people adapt to a heterogeneous environment and can adapt and relativize their own views on ethnicity and religion, thereby giving space to others. In this way, mamapas lewu can be interpreted as restoring balance between humans and nature, fellow humans and humans with God.